Implementasi Kebijakan Pemerintah Daerah Terhadap Pembangunan Pasar Modern Rufei Kota Sorong - Basri, La; Fransiskus Sagrim, Felix; Satu, Satu; Rusdi, Rusdi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to explain what is related to the Implementation of Regional Government Policy in the construction of the Rufei Modern Market in Sorong City by looking at aspects of government needs and the desires of traders. To obtain data in the field, the method used in this research is descriptive qualitative which is based on the problem to be researched, data was obtained by observation, interviews and literature study. Then the data is analyzed descriptively using available theories. This research shows that the government has made every effort to create comfort when shopping by presenting a more well-organized market, namely the Modern market in Rufei village, Sorong City, where people will be relocated from the previous market, namely the Boswesen market, to the Modern market. Rufei, however, there was an incident that occurred when the traders were relocated on the grounds that the market was not suitable to be occupied, especially in terms of road access to the market, comfort, security and unstable purchasing power of the community, which caused losses for the traders.